A Robust, Gram-Scale and High-Yield Synthesis of MDP Congeners for Activation of the NOD2 Receptor and Vaccine Adjuvantation - Khan, Farooq-Ahmad; Yaqoob, Sana; Qasim, Muhammad Wasim; Ali, Shujaat; Wang, Yan; Jiang, Zi-Hua (Synthesis, 2023)
The bacterial peptidoglycan (PGN) constituent muramyl dipeptide (MDP) and its congeners possess immuno-adjuvant activity, and find applications in vaccines to potentiate the immune response of antigens. It confers non-specific resistance towards pathogenic infections and defense against tumors. In this work, the parent MDP molecule is re-designed by replacing its carbohydrate moiety with an immunoregulatory xanthine scaffold, while conserving the l-d configuration of the pharmacophore. Alkyl chains are introduced at the C-terminus of d-isoglutamine to help the molecules access cytoplasmic NOD2 receptors and activate the innate immune system. Lipophilic MDP congeners are thus obtained by adopting a direct or indirect convergent synthetic route with overall yields of >50%. We found that an indirect approach can reliably be implemented on gram scale, thereby unlocking access to substantial amounts of pathogen-associated molecular patterns for in vivo studies, which will accelerate the development of NOD2 immuno-adjuvants against viral and bacterial infections.
Keywords: NOD2; vaccine; adjuvant; muramyl; peptides